Efficacy and Safety of Pancreatic Juice Cytology with Synthetic Secretin in Diagnosing Malignant Intraductal Papillary Mucinous Neoplasms of the Pancreas - Yohei Takeda; Kazuya Matsumoto; Takumi Onoyama; Taro Yamashita; Hiroki Koda; Wataru Hamamoto; Yuri Sakamoto; Takuya Shimosaka; Shiho Kawahara; Yasushi Horie; Hajime Isomoto (Diagnostics, 2022)
The risk of malignant transformation of intraductal papillary mucinous neoplasm (IPMN) is presently assessed using imaging, which remains unsatisfactory. Given the high viscosity of pancreatic juice, pancreatic juice cytology (PJC) is considered an investigational procedure. We previously demonstrated that the diagnostic performance of PJC was improved via synthetic secretin loading in pancreatic ductal carcinoma. This study aimed to evaluate the efficacy of synthetic secretin-loaded PJC (S-PJC) for IPMN. The usefulness and safety of S-PJC were prospectively evaluated in 133 patients with IPMN. Overall, 92, 12, and 26 patients had branch duct, main duct, and mixed-type lesions, respectively. The risk classifications based on the 2017 international consensus guidelines were high-risk stigmata, worrisome features, and no risk in 29, 59, and 45 patients, respectively. Synthetic secretin loading improved the sensitivity of PJC from 50.0% to 70.8%. Complications included 13 (9.8%) cases of mild pancreatitis, 1 (0.8%) case of acute cholangitis, and 1 (0.8%) case of Mallory–Weiss syndrome, all of which resolved with conservative treatment. In conclusion, synthetic secretin-loaded PJC improved the diagnostic performance of cytology for malignant IPMN. We recommend using synthetic secretin-loaded PJC for the preoperative pathological diagnosis of malignant IPMN in clinical settings.